1996
DOI: 10.1093/nar/24.22.4407
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a (CUG)n Triplet Repeat RNA-Binding Protein and Its Expression in Myotonic Dystrophy

Abstract: Myotonic dystrophy (DM) is an autosomal dominant neuromuscular disease that is associated with a (CTG)n repeat expansion in the 3'-untranslated region of the myotonin protein kinase (Mt-PK) gene. This study reports the isolation and characterization of a (CUG)n triplet repeat pre-mRNA/mRNA binding protein that may play an important role in DM pathogenesis. Two HeLa cell proteins, CUG-BP1 and CUG-BP2, have been purified based upon their ability to bind specifically to (CUG)8 oligonucleotides in vitro. While CUG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
390
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 423 publications
(407 citation statements)
references
References 43 publications
13
390
1
Order By: Relevance
“…[11][12][13] This deregulation of CUGBP1 results in delay of skeletal muscle differentiation and insulin resistance in DM1 disease. Since the expression of antisense RNA restored efficiency of muscle differentiation and glucose uptake (Figures 4 and 5, and Table 1), we next examined whether the antisense RNA brings CUGBP1 expression to the normal levels.…”
Section: Cugbp1 Levels In Infected Dm1 Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13] This deregulation of CUGBP1 results in delay of skeletal muscle differentiation and insulin resistance in DM1 disease. Since the expression of antisense RNA restored efficiency of muscle differentiation and glucose uptake (Figures 4 and 5, and Table 1), we next examined whether the antisense RNA brings CUGBP1 expression to the normal levels.…”
Section: Cugbp1 Levels In Infected Dm1 Cellsmentioning
confidence: 99%
“…[2][3][4] At the molecular levels, the DM1 phenotype is most likely caused by a complex molecular pathogenesis, including deficiency of myotonic dystrophy myotonin kinase (DMPK) protein, [5][6][7] haplo-insufficiency of a neighboring homeobox gene (particular the DM locus-associated homeodomain protein (DMAHP/Six 5 gene) 8 and the WD-repeat gene (DMWD) 9 and a trans-dominant misregulation of RNA homeostasis. [10][11][12][13][14][15][16] Recent experiments from transgenic mice, expressing an untranslated expanded CUG repeat under the control of the human skeletal actin promoter, showed that expanded CUG repeats are sufficient to generate DM1 muscle phenotype. 17 These data suggest that misregulation of RNA homeostasis may play a major role in DM1 muscle pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…The first protein that prompted researchers to look for the mechanism of aberrant splicing in DM1 was the CUGBP1 (Timchenko et al, 1996a(Timchenko et al, , 1996bPhilips et al, 1998). CUGBP1 is up-regulated in DM1 due to PKC (protein kinase C) pathway activation and subsequent CUGBP1 protein hyperphosphorylation and stabilization (KuyumcuMartinez et al, 2007).…”
Section: Nuclear Rna Retentionmentioning
confidence: 99%
“…[19][20][21] CELF1 interacts with the DMPK transcript, in particular with the (CUG) n repeat. 14 In a mouse model overexpressing CELF1, several typical histological and mis-splicing features of DM were demonstrated. 22 The second candidate, MBNL1, is known to bind to the expanded CUG repeat and to colocalize with the nuclear RNA foci, causing a local reduction and therefore loss of function of MBNL1 protein because of sequestration and binding to the repeat tract in the nuclear foci.…”
Section: Introductionmentioning
confidence: 99%
“…Two proteins that bind to repeat-expanded RNA are CELF1 (CUGBP, Elav-like family member 1) 14 and MBNL1 (muscleblind-like splicing regulator 1). 12 In DM muscle, a downregulation of MBNL1 function and an upregulation of CELF1 function was shown.…”
Section: Introductionmentioning
confidence: 99%